The Effectiveness of Role Play in Teaching Speaking Skill of The Eleventh Grade Students at SMAN 19 Makassar - Muldi Lumiling; Muliaty Ibrahim; Vivit Rosmayanti (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2023)
This study aims to determine the effectiveness of role-playing in teaching speaking skills to students of class XI 19 Senior High School Makassar, and whether there is a significant difference between students who are trained in speaking skills using conventional methods and students who use role-playing techniques. This study uses a quantitative approach, namely experimental research with a pre-test and post-test research design and the sample of this study is 60 students. Researchers used two clasess and experimental class using role-playing techiquess and a control class using concetional methods. Meanwhile, in the last stage, the researcher gave a post-test in the same class to find out whether the role-playing techiquess was effective in teaching students speaking skills in the experimental class. The results of this study show the average pre-test in the experimental class (59.87%) and the control class (60.93%). The post-test average of the experimental class (84.40%) was higher than that of the control class (64.53%). This means that there is a difference between students who use role-playing techniquess abd students who uses conventional techniquess. Thus, teaching speaking using role-playing techniquess has a significant effect on improving students speaking skills. Therefore, it is suggested that the role-playing techniquess can be applied as an affective learning method for teachers to teach speaking skills anf for future researchers to use the same type of research under different conditions.